Co-Simulation of an Inverter Fed Permanent Magnet Synchronous Machine - Kiss, Gergely Máté; Vajda, István (Electrical, Control and Communication Engineering, 2014)
Co-simulation is a method which makes it possible to study the electric machine and its drive at once, as one system. By taking into account the actual inverter voltage waveforms in a finite element model instead of using only the fundamental, we are able to study the electrical machine's behavior in more realistic scenario. The recent increase in the use of variable speed drives justifies the research on such simulation techniques. In this paper we present the co-simulation of an inverter fed permanent magnet synchronous machine. The modelling method employs an analytical variable speed drive model and a finite element electrical machine model. By linking the analytical variable speed drive model together with a finite element model the complex simulation model enables the investigation of the electrical machine during actual operation. The methods are coupled via the results. This means that output of the finite element model serves as an input to the analytical model, and the output of the analytical model provides the input of the finite element model for a different simulation, thus enabling the finite element simulation of an inverter fed machine. The resulting speed and torque characteristics from the analytical model and the finite element model show a good agreement. The experiences with the co-simulation technique encourage further research and effort to improve the method.